Analysis results of land-use and land cover changes of Szilas catchment from 1990 - Saeidi, Sahar; Grósz, János; Sebők, András; Deganutti de Barros, Vinicius; Waltner, István (JOURNAL OF LANDSCAPE ECOLOGY, 2019)
One of the most significant and vulnerable natural resource is the accessible free land. Detection of the land-use and land cover change (LULC) is a very important information for the future aspect. Our paper is dealing with the land-use and land cover changes of Szilas catchment between 1990 and 2018. The study area is an important for the regional water management, the nature protection, the nearby residents and sever as recreational place. In this study, CORINE land cover maps of Europe from five different time periods (1990, 2000, 2006, 2012, 2018) were used to analyze the trends of LULC changes and also detect the prominent changes in different classes of LULC maps within the Szilas catchment. During the analysis, entire data set was analyzed by crosstab module to obtain land cover changes in each category and to establish the trend of changes for the study area between 1990 and 2018. According to the results, the area of the agricultural land has decreased, however, the area of the urban region has greatly increased within the catchment. During the analysis we found that, the area of the nonirrigated arable land decreased by 10%. The process of urbanization was constantly growing: industrial or commercial units by 2%, road and rail networks associated land by 2 %, discontinuous urban fabric by 3,4%, sport and leisure facilities by 1,2%.
Keywords: land-use change; land cover; CORINE; Szilas catchment